Science Learning in Environmental Care Education at Teladan Kindergarten, Sukoharjo - B Burhanudin; Sri Katoningsih (Universitas Muhammadiyah Surakarta, 2025)
Science learning in environmental education for early childhood at Teladan Kindergarten Sukoharjo. The purpose of this study was to determine how science learning is implemented to instill environmental attitudes and behaviors in kindergarten children. This study explored the implementation process, the learning methods used, their effectiveness, and the support from the principal, teachers, and parents in developing children's science process skills and scientific literacy based on environmental education. This study also examined the challenges faced and strategies to overcome them in the context of science learning and environmental education for early childhood. This research method used a qualitative approach with a phenomenological design on the subjects of children, teachers, principals, and parents. Data were collected through observation, interviews, and documentation during the period of July to September 2025. The results of the study indicate that science learning based on simple experiments and hands-on practice is effective in improving children's knowledge, attitudes, and behaviors of environmental concern. Principal support, teacher creativity, and parental involvement are important factors in the success of this learning. Obstacles encountered include limited learning media and time; however, various strategies such as the use of simple tools and improved teacher training can overcome these. This study provides conceptual and practical contributions to the development of environmentally-based science learning for early childhood and recommends improvements in learning media, parental involvement, and collaboration with environmental communities.